Metabolic interplay of SCFA’s in the gut and oral microbiome: a link to health and disease - Nireeksha; Alexander Maniangat Luke; Alexander Maniangat Luke; Suchetha Kumari N; Mithra N. Hegde; Nishmitha N. Hegde (Frontiers in Oral Health)
Short-chain fatty acids (SCFAs), primarily acetate (C2), propionate (C3), and butyrate (C4), are crucial microbial metabolites formed by the fermentation of dietary fibers by gut microbiota in the colon. These SCFAs, characterized by fewer than six carbon atoms, serve as an essential energy source for colonic epithelial cells and contribute approximately 10% of the body's total energy requirement. They are central to maintaining gut health through multiple mechanisms, including reinforcing intestinal barrier function, exerting anti-inflammatory effects, regulating glucose and lipid metabolism, and influencing host immune responses. Butyrate, in particular, plays a pivotal role in protecting the gut mucosa and modulating inflammatory processes. Beyond their intestinal functions, SCFAs affect systemic metabolic outcomes such as body weight regulation and appetite control by modulating the secretion of gut hormones and interacting with G-protein coupled receptors. Despite strong experimental evidence, mainly from animal models, clinical applications of SCFA modulation remain in preliminary stages, with limited translational findings in human therapeutics.In parallel, the oral microbiome also produces SCFAs, such as propionic, butyric, isobutyric, and isovaleric acids, as metabolic by-products in biofilm ecosystems like dental plaque. These acids contribute to interspecies communication, “cross-feeding” dynamics, and possibly biofilm stability or pathogenicity, especially in caries and periodontal disease. SCFAs in the oral cavity may act as signaling molecules or competitive factors, modulating microbial behavior and ecological balance within the oral niche. Collectively, these insights highlight SCFAs as integral to host-microbiota interactions, both in the gut and oral environments, with potential implications for targeted microbiome-based therapies in health and disease.